WSI European Collecitve Bargaining Report 2021/2022: Collective bargaining in times of crisis, war, and inflation - Malte Lübker; Thilo Janssen (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2022)
Slackening growth, an upsurge in inflation, and the unpredictable course and consequences of the war in Ukraine have combined to create an uncertain and challenging outlook for collective bargaining in Europe. For employees, the subdued pace of pay growth in all European Union Member States has now culminated in falls in real wages, in some cases on a substantial scale, putting pressure on trade unions to offset these through higher pay settlements. At the same time, employers have warned against substantial pay rises, pointing to the risks of a wage-price spiral - despite the fact that, as yet, there is no evidence that pay has been a factor in current inflationary pressures. Achieving a compromise between these divergent standpoints is also made more difficult by the fact that the institutions of collective bargaining now have only limited scope in many countries. At the same time, the outcomes of collective bargaining can have far-reaching distributional effects.
Keywords: 330; Konjunkturpolitik/-prognose; Konjunktur/Finanzmärkte; Wirtschaft